2011
DOI: 10.1111/j.1600-079x.2011.00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin alleviates lipopolysaccharide-induced hepatic SREBP-1c activation and lipid accumulation in mice

Abstract: A link between endotoxemia and nonalcoholic fatty liver disease (NAFLD) has been demonstrated in human and rodent animals. Nevertheless, the molecular mechanisms of endotoxin-evoked NAFLD remain poorly understood. We hypothesize that reactive oxygen species (ROS) mediate lipopolysaccharide (LPS)-evoked hepatic lipid accumulation. Melatonin is an antioxidant. In the present study, we investigated the effects of melatonin on LPS-induced hepatic lipid accumulation. We showed that a single dose of LPS significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 55 publications
4
38
2
Order By: Relevance
“…After adjusting for HFD and duration of melatonin use, the lipidemic serum markers (TC, TG, LDL and HDL) were higher in rats on HFD without melatonin than in rats on HFD receiving melatonin, but this difference did not reach statistical significance. This is in contrast to the findings of Pan et al [14] and Chen et al [23] who found significantly reduced TC and TG levels in rats given a moderate or high dose of melatonin (5 or 10 mg/kg), and also to the findings of Hoyos et al [36] who found significantly reduced levels of TC and LDL in the melatonin groups. However, our findings match those of the latter study as it concerns the TG levels.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…After adjusting for HFD and duration of melatonin use, the lipidemic serum markers (TC, TG, LDL and HDL) were higher in rats on HFD without melatonin than in rats on HFD receiving melatonin, but this difference did not reach statistical significance. This is in contrast to the findings of Pan et al [14] and Chen et al [23] who found significantly reduced TC and TG levels in rats given a moderate or high dose of melatonin (5 or 10 mg/kg), and also to the findings of Hoyos et al [36] who found significantly reduced levels of TC and LDL in the melatonin groups. However, our findings match those of the latter study as it concerns the TG levels.…”
Section: Discussioncontrasting
confidence: 57%
“…The putative mechanism of the beneficial effect of melatonin on NAFLD in rats on HFD is the decrease of lipid peroxidation and the limitation or prevention of oxidative stress. Melatonin's antioxidant repertoire includes: its stimulation of antioxidant enzymes [16] , the regulation of gene transcription for antioxidant enzymes [17] , its direct free radical scavenger action [18] , the stimulation of glutathione synthesis [19] , its ability to augment the activities of other antioxidants [20] , the protection of antioxidative enzymes from oxidative damage [21] , its action on the mitochondrial respiratory chain activity whereby melatonin lowers the electron leakage and reduces the generation of free radicals [22] , and finally its significant attenuation of LPS-induced sterol regulatory element-binding protein (SREBP)-1c activation and expression of SREBP1c target genes that prevents LPS-induced hepatic lipid accumulation [23] . Lipid peroxidation, and peroxidation of membrane lipids, links steatosis to steatohepatitis, with its attendant necroinflammation, liver cell necrosis, increased ALT and AST levels, and fibrosis [24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis showed that SREBP-1c was activated in LPS-treated mice. In agreement with hepatic SREBP-1c activation, the expression of FAS and ACC, 2 SREBP-1c target genes was significantly up-regulated in the liver of mice injected with LPS (Chen et al, 2011). Intraperitoneal injection of LPS to induce TNF-a expression accelerated hepatic fat accumulation.…”
Section: Discussionsupporting
confidence: 52%
“…Ravindranath et al (2003) found that endotoxic shock in 10-day-old rat pups induced a systemic inflammatory response with a decrease in FA metabolism, which may contribute to myocardial failure. Chen et al (2011) showed that a single dose of LPS significantly increased hepatic triglyceride content and caused hepatic lipid accumulation in mice. Further analysis showed that SREBP-1c was activated in LPS-treated mice.…”
Section: Discussionmentioning
confidence: 99%